"Deveiling" Body Stories: Muslim Girls Negotiate Visual, Spatial, and Ethical "Hijabs" - Hamzeh, Manal (Race, Ethnicity and Education, 2011)
This article describes a collaborative research project that took place in two south‐western US border towns and sought to understand how four muslim Footnote 1 girls (age 14–17) expressed and negotiated their bodily learning experiences. Drawing on both the work of arab–muslim critical feminist Fatima Mernissi who utilized classical Islamic tools of research and my positionalities as arabyyah‐muslimah, I used insider’s methods to discuss how three hijabs (veils) – the visual, spatial, and ethical – acted as a central genderizing discourse that challenged the girls’ learning opportunities. This article shows how the girls’ parents enforced these three hijabs; how the girls questioned and deveiled the hijabs in their dress, mobility in public places, and physical behavior around boys. This inquiry is a call for critical feminist researchers and educators to recognize how these three hijabs form a key genderizing discourse in the lives of muslim girls. It also presents the importance of: (1) working with muslim girls as agents in their own lives; (2) critical engagement with difference between researchers/educators and muslim communities; and (3) practicing a critically reflexive pedagogy of deveiling.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; corps; cours; discipline; féminisme islamique; point de vue situé; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; thématiques; états-unis; états-unis (sud)

Nous autres, les autres: difficile pluralisme - Robin, Régine (Collection Liberté grande, 2011)
Fine analyste de discours idéologiques et libre flâneuse de parcours urbanistiques, Régine Robin, historienne, sociologue, écrivain, s’est toujours préoccupée, en lisant, en écrivant et en marchant, des questions politiques d’identité, de culture et de mémoire. Arrivée à Montréal en 1977, professeur et citoyenne, pugnace républicaine devenant Canadienne et prêtant serment d’allégeance à la reine d’Angleterre (elle aurait préféré le faire sur la bible de Proust), l’auteur de La Québécoite, au bout de trente ans de résidence première, évoque, convoque et disloque tout ce qui fait qu’elle est « devenue d’ici » même si, comme elle l’écrit, « je ne me suis jamais sentie chez moi ». Dans ce livre qui inaugure la collection « Liberté grande », on trouve une indéniable et cinglante analyse du nationalisme québécois et un questionnement inquiet sur la transculture et l’écriture migrante. Bilan d’une « allophone d’origine française ».
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; immigration; lit3495; point de vue situé; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires